Space–Time Modeling of Insurgency and Counterinsurgency in Iraq - Braithwaite, Alex (Journal of quantitative criminology, 2012)
The US and its Coalition partners concluded combat operations in Iraq in August 2010. Rather surprisingly, little empirical evidence exists as to the factors that contributed to the ebb and flow in levels of violence and the emergence and disappearance of hot spots of hostilities during the campaign. Building upon a tradition of criminology scholarship, recent work demonstrates that Improvised Explosive Device (IED) attacks are clustered in space and time and that these trends decay in a manner similar to that observed in the spread of disease and crime. The current study extends this work by addressing a key potential correlate of these observed patterns across Iraq—namely, the timing and location of a variety of Coalition counterinsurgency (COIN) operations. This is achieved by assessing the co-evolving space–time distributions of insurgency and counterinsurgency in the first 6 months of 2005. To do so, we employ a novel analytic technique that helps us to assess the sequential relationship between these two event types. Our analyses suggest that the number of COIN operations that follow insurgent IED attacks (moderately) exceeds expectation (assuming that events are independent) for localities in the vicinity of an attack. This pattern is more consistent than is observed for the relationship in the opposite direction. The findings also suggest that less discriminatory COIN operations are associated with an elevated occurrence of subsequent insurgency in the vicinity of COIN operations in the medium to long term, whilst for more discriminatory and capacity-reducing COIN operations the reverse appears to be true.